2012
DOI: 10.5539/gjhs.v4n6p170
|View full text |Cite
|
Sign up to set email alerts
|

Food Polyamine and Cardiovascular Disease -An Epidemiological Study-

Abstract: The purpose of this study was to examine the contribution of dietary polyamines toward preventing cardiovascular disease (CVD). Age-standardized mortality rates as well as other relevant information regarding individuals with CVD were gathered from the World Health Organization and the International Monetary Fund in 48 different European and other Western countries. Food supply data were collected from the database of the United Nations, and the amount of dietary polyamines was estimated by using polyamine con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 34 publications
0
38
1
Order By: Relevance
“…Although our findings suggest that activation of TCPTP might be beneficial in TGF-β-driven fibrotic diseases, spermidine is not a selective TCPTP activator. It has previously been shown that long-term polyamine intake can have both beneficial and deleterious effects: it can decrease mortality and incidence of colon cancer in aged mice (51) and protect against cardiovascular mortality in humans (52), but can also cause a decline in human renal function (53). Nevertheless, our findings support the need to generate more selective and safer TCPTP activators for the prevention and treatment of TGF-β-mediated kidney disease.…”
Section: Discussioncontrasting
confidence: 47%
“…Although our findings suggest that activation of TCPTP might be beneficial in TGF-β-driven fibrotic diseases, spermidine is not a selective TCPTP activator. It has previously been shown that long-term polyamine intake can have both beneficial and deleterious effects: it can decrease mortality and incidence of colon cancer in aged mice (51) and protect against cardiovascular mortality in humans (52), but can also cause a decline in human renal function (53). Nevertheless, our findings support the need to generate more selective and safer TCPTP activators for the prevention and treatment of TGF-β-mediated kidney disease.…”
Section: Discussioncontrasting
confidence: 47%
“…Their antioxidant activities protect lipids and proteins, stabilize the negative charges of DNA and RNA transcription and protect DNA from oxidative damage from gamma, x and UV rays [21]. Spermine and spermidin have significant antiglycation activity at physiological concentrations, protect against chronic diseases [22] and have been related to obesity [23,24]. Polyamines are actively synthesized in the mammary gland during lactation.…”
Section: Polyaminesmentioning
confidence: 99%
“…The study was an ecological investigation, and the data used do not indicate the amount of foods actually consumed; however, as the food supply likely reflects the food demand, the analysis using relative amounts may reflect the food preferences of the people in each country. The study results indicated that the Mediterranean diet preferred in Mediterranean countries is associated with increased polyamine concentrations (Binh et al, 2011;Soda et al, 2012). Notably, although olive oil and wine, two components of the Mediterranean diet, contain no polyamines, people who prefer these ingredients also prefer foods rich in polyamines per calorie (Binh et al, 2011).…”
Section: Epidemiologic Surveys and Dietary Polyaminesmentioning
confidence: 99%